RECORDING VIRTUAL TEAMS USING THE SYSTEM OF ORGANIZATIONAL TERMS FOR ARTIFICIAL MANAGEMENT IMPLEMENTATION. RESEARCH RESULTS - Olaf Flak, (PEOPLE: International Journal of Social Sciences, 2025)
The paper describes the potential of artificial management in virtual teams, focusing on how AI can replicate managerial actions typically performed by human team leaders and members. The research is driven by two main questions: (1) What theoretical framework should be used to document managerial actions? and (2) What tools can effectively measure and build knowledge about these actions? Methodology The study adopts a qualitative case study approach, supported by a long-term non-participant observation of a virtual team consisting of a manager and three members. It applies the system of organizational terms, rooted in Wittgenstein’s philosophy, to record team behaviors. Data were collected using TransistorsHead.com – 10 online management tools that tracks the sequence and outcomes of team actions over time. Findings.The system of organizational terms successfully identified and categorized specific managerial actions. TransistorsHead.com enabled real-time tracking and visualization of team dynamics across 10 categories of managerial actions. The study confirmed the feasibility of capturing complex human patterns of behavior aimed at artificial management implementation. Conclusion The research demonstrates that managerial behaviors in virtual teams can be systematically recorded and analyzed. These findings are the foundations for implementing artificial management systems capable of autonomously performing core team actions.